2023
DOI: 10.3390/jof9010068
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of Promising Indigenous Entomopathogenic Fungal Isolates against Red Palm Weevil, Rhynchophorus ferrugineus (Coleoptera: Dryophthoridae)

Abstract: The rate of the sounds (i.e., substrate vibrations) produced by the movement and feeding activity of red palm weevil (RPW) pest infestations in a date palm tree was monitored over time after trees were separately treated with injection of entomopathogenic fungal isolates, Beauveria bassiana and Metarhizium anisopliae, or water treatment as the control. The activity sensing device included an accelerometer, an amplifier, a digital recorder, and a signal transmitter that fed the data to a computer that excluded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…This study is supportive of other studies that evaluated the effectiveness of microorganisms [44] and fungal treatments against RPW [26,45]. RPW can be managed by microorganisms that cause infection in insects [46].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study is supportive of other studies that evaluated the effectiveness of microorganisms [44] and fungal treatments against RPW [26,45]. RPW can be managed by microorganisms that cause infection in insects [46].…”
Section: Discussionsupporting
confidence: 82%
“…In another study, RPW movement and feeding activities in date palm trees produced significantly lower impulse burst rates [20] after treatment with B. bassiana. It is possible that infected RPW larvae within date palm trees become weaker, lose their appetite, and move more slowly [44,47]. It should be noted that spores of fungal isolates with weak germination, low pathogenicity, and low water solubility are not recommended for use against the RPW [2].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of this approach, coupled with its successful application in innovative bioacoustics tasks, has been demonstrated in prior research focused on birdsong classification [17]. Therefore, a future direction is to have our approach-which is very fast and very low in power consumption-do the heavy screening of searching for needles in the hay and direct only a small subset to heavy deep-learning models that will scrutinize these cases especially when one applies low thresholds (that produce false alarms) with the aim to detect early instars and low infestation load [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Since D. borassi and R. palmarum have been recognized as pests of economic importance for the crops of Bactris gasipaes and Cocos nucifera (Bautista-Giraldo et al 2020 ; Gaviria et al 2021 ; Gutiérrez et al 2023 ), the results obtained with the Bv065 strain show great potential for its use in the field, where different dissemination strategies can be employed such as trunk applications (Güerri-Agulló et al 2010 ), passage traps for the inoculation of adults (Dembilio et al 2018 ), release of contaminated males (León Martínez et al 2019 ); where the control objective is the adults. Additionally, exploratory studies have shown the potential use of B. bassiana in endotherapy (i.e., trunk injection) for the control of weevil larvae inside the palms (Sutanto et al 2023 ; Husain et al 2024 ).…”
Section: Discussionmentioning
confidence: 99%